Application of Quiz Team Learning Methods to Increase Students Learning Motivation and Learning Outcomes in Class XI IPS SMA Negeri 1 Sawerigadi - Tamburu, La (Journal of Teaching of English, 2021)
This research aimed to increase learning motivation and learning outcomes in English with cause and effect material by applying the quiz team learning method. This research used Classroom Action Research (CAR) which was carried out in two cycles with four stages, namely planning, action, observation, and reflection. The subjects in this study were students of class XI Social Sciences at SMA Negeri 1 Sawerigadi, West Muna Regency, Southeast Sulawesi Province in semester 1 of the 2017/2018 academic year which involved 22 students. The research objective was learning motivation and learning outcomes in English with cause and effect by applying the quiz team learning method. The research instrument was a written test. Data analysis used was descriptive analysis technique of comparison with percentage. The results of this study indicate that there is an increase in learning motivation and English learning outcomes for students' cause and effect material seen from the average score. The average score of increasing learning motivation and learning outcomes in English for cause and effect material with the application of the Quiz Team learning method is shown in the pre-cycle the average value is 61.59, in the Cycle Iit increases to 71.36 and in the Cycle II it increases with an average score. 83.86 average. In terms of minimum completeness criteria (KKM) in pre-cycle students who achieve KKM are 45.45%. In the first cycle, it increases to 63.64% and in the Cycle II it increases to 86.36% while the percentage in learning motivation in the Cycle Iis 58, 52% increases to the Cycle II to 85.80%. The conclusion that can be drawn in this study is that the application of the Quiz Team learning method has increased students learning motivation and learning outcomes, so it is feasible to be applied in SMA Negeri 1 Sawerigadi.